Effects of feeding 25-hydroxyvitamin D3 with an acidogenic diet during the prepartum period in dairy cows: Mineral metabolism, energy balance, and lactation performance of Holstein dairy cows - A.S. Silva; C.S. Cortinhas; T.S. Acedo; M.J.F. Morenz; F.C.F. Lopes; M.B. Arrigoni; M.H. Ferreira; T.L. Jaguaribe; L.D. Ferreira; V.N. Gouvêa; L.G.R. Pereira (Journal of Dairy Science, 2022)
ABSTRACT: Our objective was to determine the effects of feeding 25-hydroxyvitamin D3 [25(OH)D3], or vitamin D3 (cholecalciferol) on plasma, mineral, and metabolite concentrations, mineral balance, mineral excretion, rumination, energy balance, and milk production of dairy cows. We hypothesized that supplementing 3 mg/d of 25(OH)D3 during the prepartum period would be more effective than supplementing vitamin D3 at the National Research Council (2001) levels to minimize calcium imbalance during the transition period and improve milk production of dairy cows. Forty multiparous, pregnant nonlactating-Holstein cows were enrolled in this study. Body weight, body condition score, parity, and milk yield in the previous lactation (mean ± standard deviation) were 661 ± 59.2, 3.46 ± 0.35, 1.79 ± 0.87, and 33.2 ± 6.43 kg/d, respectively. Cows were enrolled into the blocks (n = 20 for each treatment) at 30 d of the expected day of calving to receive an acidogenic diet (373 g/kg of neutral detergent fiber and 136 g/kg of crude protein, dry matter basis; −110 mEq/kg) associated with the treatments: (1) control (CTRL), vitamin D3 at 0.625 mg/d (equivalent to 25,000 IU of vitamin D3/d) or (2) 25(OH)D3 at 3 mg/d (equivalent to 120,000 IU of vitamin D3/d). All cows were fed with the base ration for 49 d after calving. Blood samples were taken on d 7, 0, 1, 2, 21, and 42, relative to calving. No effect of treatment was observed for prepartum dry matter intake or body condition score. A trend for increase of ionized Ca was observed for the cows fed 25(OH)D3, compared with the CTRL, but no effect of treatment was detected for total Ca or total P. Feeding 25(OH)D3 increased colostrum yield. The plasmatic concentration of 25-hydroxyvitamin D3 was increased with 25(OH)D3 supplementation. 25-Hydroxyvitamin D3 supplementation increased plasma glucose concentration at parturition. The postpartum dry matter intake was not influenced by treatments. Feeding 25(OH)D3 increases milk yield, 3.5% fat-corrected milk, and energy-corrected milk and improves milk yield components in early lactation. Overall, these findings suggest that 25(OH)D3 at 3 mg/d can improve the energy metabolism and lactation performance, compared with the current-feeding practice of supplementing vitamin D3 at 0.625 mg/d.